Avaliação de aspectos psicogenéticos do nível de análise heurística de crianças por meio do jogo lig-4 - Oliveira, Thaís Prando (2012)
This research has investigated, in a psychogenetic approach, childrens cognitive function aspects through a game of rules based on Piagets theory. Twenty-one children participated in this study, from both genders, ages varying from eight to twelve, from a public elementary school from Vitória ES. Data gathering occurred in three meeting per pair, utilizing the game lig-4 and a protocol containing questions and problem-situations. The first meeting was made in two phases: learning and game practice. The second one, in two moments, being one destined to game practice and, the other one, to the first assessment of heuristic analysis level. On the third meeting there were more game practice and the second assessment on heuristic analysis level. Data was analyzed using heuristic analysis levels formulated in relation to Cognitive Systems I and II proposed by Piaget. Among the results, it was verified that the situation destined to the first assessment and game practice expansion did not offer an expressive improvement on heuristic analysis level in the participants from both ages on the second assessment. However, comparing both participants performances, it was stated that the twelve-year-olds performances was superior than the eight-year-olds , taking in consideration that on Cognitive System I they ve achieved more complex levels than on Cognitive System II. It was concluded that, the game lig-4 was adequate to analyze Cognitive Systems, providing resources for evaluation and intervention jobs.